Tackling Childcare : The Business Case for Employer-Supported Childcare in Sri Lanka - International Finance Corporation (World Bank, Washington, DC, 2019)
This report Tackling Childcare: The Business Case for Employer-supported Childcare in Sri Lanka responds to IFC client and partner demand for country-specific business case evidence on childcare and practical guidance on putting ideas into practice. It features I O case studies of companies across sectors—including in the country's key industries such as apparel and information technology—to highlight why employers should consider supporting their employees' childcare needs. The report shows that building an onsite creche is not the only way forward, as there are many different models through which employers can support their employees. The models the companies choose depend on what they can offer-while still gaining business benefits. This publication reaches hundreds of employers in the country, so they can learn from our partners' experience and replicate what works. It is also a call to action, urging key stakeholders to invest in childcare solutions and support the infrastructure that allows childcare providers to grow at the scale that is needed to support the demand, and generate.